Psychosocial long-term outcome in patients with psychogenic non-epileptic seizures - Walther, Katrin; Volbers, Bastian; Erdmann, Laura; Kurzbuch, Katrin; Lang, Johannes; Müller, Tamara; Reindl, Caroline; Schwarz, Michael; Schwab, Stefan; Hamer, Hajo (Seizure-European Journal of Epilepsy, 2020)
Purpose: To evaluate psychosocial long-term outcome in patients diagnosed with psychogenic nonepileptic seizures (PNES) and to predict outcome of PNES, economic status, and quality of life (QoL) at follow-up. Methods: Patients diagnosed with PNES in the video-EEG-monitoring unit at our Epilepsy center between 2002–2016 were contacted by phone 1–16 years after communicating the diagnosis. Patients underwent a structured interview asking for current PNES status, psychosocial situation (economic status, marital status, setting of living, driving), depression, and QoL. Results: Of 70 PNES patients without comorbid epilepsy (age: 41.1 ± 13.5 years; 74 % female, follow-up: 5.2 ± 4.2 years), 23 patients (33 %) reported to be free of PNES during the last 12 months. Patients with cessation of PNES were younger at PNES onset (p < .01) and diagnosis (p < .01) and had a higher education (p < .05). At follow-up, the proportion of economically active patients only increased in individuals with cessation of PNES (p < .001) while an increased number of patients with persisting PNES relied on governmental support (p < .001). Cessation of PNES was associated with better mood (p < .01) and QoL (p < .001). In multiple regression models, cessation of PNES was only predicted by younger age at onset, while good economic outcome was determined by younger age and good economic status at diagnosis and cessation of PNES at follow-up. Good QoL at follow-up was predicted by low depressive symptoms, freedom of PNES, and economic activity at follow-up. Conclusion: Long-term outcome in patients with PNES remains to be poor and the majority of patients continue to have PNES. Cessation of PNES was associated with good economic outcome, mood, and QoL.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Employment; Long-term outcome; Marital status; Mood; Psychogenic non-epileptic seizures; Quality of life